The migration and differentiation of hUC-MSCsCXCR4/GFP encapsulated in BDNF/chitosan scaffolds for brain tissue engineering. (5th May 2016) - Huang, Chuanjun; Zhao, Longxiang; Gu, Jun; Nie, Dekang; Chen, Yinan; Zuo, Hao; Huan, Wei; Shi, Jinlong; Chen, Jian; Shi, Wei
Abstract: We previously developed a biomaterial scaffold that could effectively provide seed cells to a lesion cavity resulting from traumatic brain injury. However, we subsequently found that few transplanted human umbilical cord mesenchymal stem cells (hUC-MSCs) are able to migrate from the scaffold to the lesion boundary. Stromal derived-cell factor-1 α and its receptor chemokine (C-X-C motif) receptor (CXCR)4 are chemotactic factors that control cell migration and stem cell recruitment to target areas. Given the low expression level of CXCR4 on the hUC-MSC membrane, lentiviral vectors were used to generate hUC-MSCs stably expressing CXCR4 fused to green fluorescent protein (GFP) (hUC-MSCs CXCR4/GFP ). We constructed a scaffold in which recombinant human brain-derived neurotrophic factor (BDNF) was linked to chitosan scaffolds with the crosslinking agent genipin (CGB scaffold). The scaffold containing hUC-MSCs CXCR4/GFP was transplanted into the lesion cavity of a rat brain, providing exogenous hUC-MSCs to both lesion boundary and cavity. These results demonstrate a novel strategy for inducing tissue regeneration after traumatic brain injury.